Executive compensation and the susceptibility of firms to hostile takeovers. An empirical investigation of the U.S. oil industry - Eric Nowak; Michael H. Haid (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 1999)
We investigate the suggested substitutive relation between executive compensation and the disciplinary threat of takeover imposed by the market for corporate control. We complement other empirical studies on managerial compensation and corporate control mechanisms in three distinct ways. First, we concentrate on firms in the oil industry for which agency problems were especially severe in the 1980s. Due to the extensive generation of excess cash flow, product and factor market discipline was ineffective. Second, we obtain a unique data set drawn directly from proxy statements which accounts not only for salary and bonus but for the value of all stock-market based compensation held in the portfolio of a CEO. Our data set consists of 51 firms in the U.S. oil industry from 1977 to 1994. Third, we employ ex ante measures of the threat of takeover at the individual firm level which are superior to ex post measures like actual takeover occurrence or past incidence of takeovers in an industry. Results show that annual compensation and, to a much higher degree, stock-based managerial compensation increase after a firm becomes protected from a hostile takeover. However, clear-cut evidence that CEOs of protected firms receive higher compensation than those of firms considered susceptible to a takeover cannot be found.
urn:nbn:de:hebis:30-18184
Keywords: G3; G34; J33; 330; Compensation Contracting; Executive Compensation; Oil Industry; Takeovers; Corporate Governance; Übernahme; Führungskräfte; Vergütungssystem; Mineralölwirtschaft; Schätzung; USA